THE USING OF COOPERATIVE MODEL TIPE GROUP INVESTIGATION BY MULTIMEDIA IN IMPROVING SCIENTIFIC ATITTUDES AND SCIENCE LEARNING RESULT IN FIFTH GRADE OF SDN TANUHARJO - Khoerunisa, Evi (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Using of Cooperative Model Tipe Group Investigation by Multimedia in Improving Scientific Atittudes and Science Learning Result in Fifth Grade of SDN Tanuharjo. The aims of the research is to improve scientific atittudes and science learning result in fifth grade of SDN Tanuharjo using of cooperative model tipe Group Investigation by multimedia. This research is a collaborative Classroom Action Research (CAR) conducted in three cycles, each cycle of the two meeting. Research prosedure include of planning, acting, observing, and reflecting. Subject of this research are 28 students. The results showed that the use of kooperative model tipe Group Investigation by multimedia  can improve scientific atittudes and science learning result in fifth grade of SDN Tanuharjo.Key Words: Group Investiigation, multimedia, Scientific Atittudes